Proyecto de Ley de Unión Civil entre personas del mismo sexo. Posiciones a favor y en contra - González Suarez, Mirta (2012)
The "Law on Civil Unions of Same-Sex" has caused a strong polarization of opinios. For this study was chosen an exploratory methodology involving the application of 94 structured interviews of people from different social groups. It is presented the arguments agree and against, the perceptions of the group, the possible effects if it is approved the project, knowledge and image of the same sex and knowledge of the law project. Some results are: religion-God-is as central in the discussion, the marriage is seen as sacred and perfect, procreation is presented as a main objective of the couples, sexuality is a source of love or sin; homosexuality is stigmatized by people against as a source of social deterioration.